Lexicon Universal Encyclopedia: Annual 1986 - Jeffrey H. Hacker (New York Lexicon Publications Inc., 1986)
Editorial Director Bernard S. Cayne
21 volumes : illustrations (some color)
"Titles of other English language editions: Lexicon universal encyclopedia, Grolier academic encyclopedia, Academic international, Grolier international encyclopedia"--CIP data sheet Academic American encyclopedia
Keywords: Encyclopedias (3GdehShYGJs; General; Encyclopedias and Dictionaries